2002
DOI: 10.1093/phr/117.2.174
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Health Care for Adults with Developmental Disabilities

Abstract: SYNOPSISObjective. The purpose of this study was to determine the health status of adults with developmental disabilities residing in community settings and the quality of the preventive, medical, dental, and psychiatric services they receive.Methods. Data were collected on a sample of 353 adults residing in Los Angeles, California, in 1997. Historical data were obtained from study subjects or caregivers, physical and dental examinations were performed, blood was drawn for analysis, and a psychiatrist reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 23 publications
(23 reference statements)
9
96
2
1
Order By: Relevance
“…An exception was mental health conditions, which were noted to decrease with age in both studies. Similar to other studies [Beange et al, 1995;Lewis et al, 2002], high rates of neurological and psychiatric conditions were observed. Comparison of their findings with comparable general US population data led the US authors to speculate that proxy reporting leads to underrecognition of health problems in persons with ID.…”
Section: Studies Using Surveyssupporting
confidence: 91%
See 4 more Smart Citations
“…An exception was mental health conditions, which were noted to decrease with age in both studies. Similar to other studies [Beange et al, 1995;Lewis et al, 2002], high rates of neurological and psychiatric conditions were observed. Comparison of their findings with comparable general US population data led the US authors to speculate that proxy reporting leads to underrecognition of health problems in persons with ID.…”
Section: Studies Using Surveyssupporting
confidence: 91%
“…Approximately one-half were medicated for behavioral problems; 96% were prescribed two or more medications and 22% were prescribed seven or more. In the United States, Lewis et al [2002] examined a representative sample of adults (mild to profound ID) living in a variety of community settings. More than a quarter of their sample had epilepsy, about half were receiving psychotropic medications, more than half were overweight or obese, and only 16% had dental status rated as "good.…”
Section: Studies Conducting Physical Examinations Of Groups Of Idmentioning
confidence: 99%
See 3 more Smart Citations